The effect of excessive penetration of welding on sand erosion pattern due to high speed gas-solid flows in elbows and reducers. (January 2022) - Hosseini, F.; Meghdadi Isfahani, A.H.; Davazdah Emami, M.; Mohseni, E.
Highlights: The effect of excessive penetration of welding and natural gas impurity particles on erosion is investigated. For high speed gas-solid flows the excessive penetration leads to powerful erosion. Erosion rate of elbows is higher than that of reducers. Abstract: The aim of the current study is to investigate the effect of excessive penetration of welding and natural gas impurity particles on increasing erosion in elbows and reducers. To this end Euler–Lagrange model is used to simulate the two-phase solid–gas flow, the Discrete Phase Model (DPM), k-ε turbulent model and DNV erosion model are used to model the solid particles, natural gas flow and erosion rate, respectively. Erosion in elbows occurs downstream of vertical welding while in reducers is weaker and occurs at the inlet. The results show that erosion rate increases by increasing excessive penetration, particles size, particles flow rate and natural gas flow rate. The effect of excessive penetration becomes more important in high speed flows containing solid particles, in such a way that reducing excess penetration from h = 3 mm to h = 0 mm, causes 45% reduction in erosion rate in elbows containing 20 m/s natural gas flows. Therefore, for high velocity impure gas flows, it is recommended to reduce the allowable excessive penetration in welding standards.